2016
DOI: 10.3892/mco.2016.840
|View full text |Cite|
|
Sign up to set email alerts
|

Sialoblastoma of the cheek: A case report and review of the literature

Abstract: Sialoblastoma is a rare salivary gland tumor that recapitulates the primitive salivary gland anlage. The authors herein report a case of sialoblastoma of a minor salivary gland, clinically presenting with progressive enlargement of a mass in the cheek of a 1-year-old female infant. Histopathologically, the mass consisted of tight clusters of basaloid cells and partially formed ductal and pseudo-ductal spaces separated by thin fibrous bands. Immunohistchemical studies demonstrated the presence of cytokeratin AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The imaging features of sialoblastoma have been documented in a few cases. On CT scan, they are detected as lobulated lesions that are isodense to muscle (11,12). On MRI, these tumors show low or intermediate signal intensity on T1-weighted images and intermediate or mildly high signal intensity on T2-weighted images, suggesting a high nucleus-to-cytoplasmic ratio (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…The imaging features of sialoblastoma have been documented in a few cases. On CT scan, they are detected as lobulated lesions that are isodense to muscle (11,12). On MRI, these tumors show low or intermediate signal intensity on T1-weighted images and intermediate or mildly high signal intensity on T2-weighted images, suggesting a high nucleus-to-cytoplasmic ratio (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…[1] Sitthichaiyakul et al observed that the median age of diagnosis was 9.8 years. [2] There have also been isolated case reports of sialoblastoma in adults. [1] The incidence is extremely rare with only single case reports being reported.…”
Section: Progressive Metastatic Sialoblastoma In a Young Child: Challenges In Treatmentmentioning
confidence: 99%
“…It is thought to arise from the retained blastemal cells in the salivary gland. [2] Sialoblastomas usually tend to progress locally, with local recurrences and rarely metastasize. [2] Irace et al did a literature review of 62 cases, of which only nine patients had metastatic disease.…”
Section: Progressive Metastatic Sialoblastoma In a Young Child: Challenges In Treatmentmentioning
confidence: 99%
See 2 more Smart Citations